Halide sulfide double-layer coated cathode material, and preparation method and application thereof
By using a halide-sulfide double-layer coating of the cathode material, the problems of high halide electrolyte density and poor oxidation stability of sulfide electrolyte in all-solid-state batteries are solved, achieving improved battery performance with high energy density, good rate performance and long cycle life.
Patent Information
- Application Number
- CN202511157363.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2025-08-19
- Publication Date
- 2025-12-09
- Estimated Expiration
- 2045-08-19
AI Technical Summary
In existing all-solid-state batteries, halide electrolytes have high density and poor air stability, while sulfide electrolytes have poor oxidation stability, resulting in high interfacial impedance and difficulty in processing in a dry environment, which affects battery performance.
A halide-sulfide bilayer coating of positive electrode material is adopted, with halide electrolyte as the middle layer to improve interfacial stability and sulfide electrolyte as the outer layer to improve chemical stability. Through specific ratios and processes, a coating layer with both high ionic conductivity and low density is formed.
It improves the energy density, rate performance, and cycle life of all-solid-state batteries, solves the problems of poor chemical stability and high density of halide electrolytes, and reduces interfacial impedance and electron transport impedance.
Smart Images

Figure SMS_1
Abstract
Description
TECHNICAL FIELD
[0001] The present application relates to the technical field of all-solid-state batteries, in particular to a halide-sulfide double-coated positive electrode material, a preparation method and application thereof, and more particularly to a halide-sulfide double-coated positive electrode material, a preparation method of the halide-sulfide double-coated positive electrode material, an all-solid-state battery and an electric device. BACKGROUND
[0002] All-solid-state batteries have greatly improved intrinsic safety due to the use of solid-state electrolytes instead of flammable organic electrolytes. Solid-state electrolytes, as the core component of all-solid-state batteries, are the key to the development of all-solid-state batteries. Solid-state electrolytes mainly include four categories: polymers, oxides, sulfides and halides. Among them, sulfide and halide electrolyte materials have become the best choice for all-solid-state battery solid-state electrolytes due to their low Young's modulus and high ionic conductivity.
[0003] Although halide electrolytes have high oxidation resistance and are compatible with high-voltage cathodes, their high density can affect the energy density of the battery, and their poor air stability makes it difficult to process electrodes containing halide electrolytes in dry environments. Although sulfide electrolytes have low density, they have poor oxidation stability and are prone to oxidation and decomposition when in contact with positive electrode materials, exacerbating the interface problems on the surface of the positive electrode.
[0004] Patent No. CN118117073A discloses a method for double-layer solid-state electrolyte coating of high-voltage positive electrode materials, but the inner layer is coated with sulfide electrolyte, which can cause interface problems with the positive electrode due to oxidation and decomposition of the sulfide electrolyte. In addition, the outer layer of halide electrolyte has poor chemical stability and cannot be processed outside the glove box.
[0005] Therefore, the present application is proposed. SUMMARY
[0006] Halide and sulfide electrolytes are the best choice for all-solid-state battery electrolytes due to their high ionic conductivity and low Young's modulus. Among them, halide electrolytes have low ionic conductivity, poor air chemical stability, high density, but strong oxidation resistance and good interface stability with positive electrode materials; sulfide electrolytes have high ionic conductivity, good air chemical stability, low density, but problems such as oxidation, element interdiffusion and space charge layer effect occur when in direct contact with positive electrode materials, resulting in large and rapidly growing interface impedance. These two types of electrolyte materials have their own advantages and disadvantages, and single electrolyte cannot meet the requirements of high-performance all-solid-state batteries.
[0007] The first object of the present application is to provide a halide sulfide double-layer coated positive electrode material, a halide electrolyte coating layer is located in the middle layer, and the high oxidation resistance thereof can realize the compatibility with the positive electrode interface, thereby avoiding the problem of large interface impedance caused by poor stability of the sulfide electrolyte directly contacting the positive electrode; the sulfide electrolyte coating layer is located in the outermost layer, and the air chemical stability is relatively good, which can meet the processing in a dry environment, and has the advantages of high ionic conductivity and low density, which is beneficial to the improvement of the rate and energy density of the full solid-state battery. The halide sulfide double-layer coated positive electrode material solves the problems of poor chemical stability of the halide electrolyte, inability to be processed and manufactured in an external environment, and high density by constructing a sulfide electrolyte coating layer on the outer layer of the halide electrolyte coating layer. The halide sulfide double-layer coated positive electrode material has high interface stability and good chemical stability. In addition, a suitable halide electrolyte coating amount can inhibit the side reaction of the sulfide and the positive electrode material, and avoid the performance deterioration problems caused by the halide environment side reaction and high density; a proper amount of sulfide electrolyte coating is beneficial to reducing the side reaction of the halide electrolyte, constructing a better ion transport path in the electrode, and avoiding the problem of large electronic transmission impedance caused by excessive coating amount.
[0008] The second object of the present application is to provide a preparation method of a halide sulfide double-layer coated positive electrode material. The halide sulfide double-layer coated positive electrode material prepared by the method has high interface stability and good chemical stability, and the preparation method has the advantages of simple operation, short process, low cost and suitability for batch production.
[0009] The third object of the present application is to provide a full solid-state battery, which has high energy density, good rate performance and long cycle life.
[0010] The fourth object of the present application is to provide an electric device.
[0011] In order to achieve the above objects of the present application, the following technical solutions are adopted:
[0012] The present application first provides a halide sulfide double-layer coated positive electrode material, which comprises a positive electrode material substrate and a halide electrolyte coating layer and a sulfide electrolyte coating layer successively coated on the positive electrode material substrate. The mass of the halide electrolyte coating layer is 0.5% to 1% of the mass of the positive electrode material substrate; the mass of the sulfide electrolyte coating layer is 2% to 5% of the mass of the positive electrode material substrate.
[0013] Further, the halide electrolyte coating layer comprises a chemical formula of Li z MX 6-v G vA material, wherein M includes at least one of Y, Yb, Zr, In, Sc, Ta and La elements, X includes at least one of Cl, Br and I elements, G includes at least one of O, N and F elements, 2<=z<=4, 0.1<=v<=0.5.
[0014] Further, the material of the sulfide electrolyte coating layer includes at least one of a first sulfide electrolyte or an oxygen-doped modified material thereof, and a second sulfide electrolyte or an oxygen-doped modified material thereof. (6-x) PS (5-x) Q (1+x) Q includes at least one of Cl, Br and I elements, 0<=x<=0.6. The second sulfide electrolyte has a chemical formula of yLi2S·(1-y)P2S5, 0.2<=y<=0.8.
[0015] Further, the positive electrode material substrate includes a polycrystalline positive electrode material and a single-crystal positive electrode material.
[0016] Further, the mass ratio of the polycrystalline positive electrode material to the single-crystal positive electrode material is 6~8:2~4.
[0017] Further, the polycrystalline positive electrode material includes secondary particles formed by aggregation of primary particles, wherein the secondary particles have a median particle size D501 of 3~7 μm, and the primary particles have a median particle size of 300~500 nm.
[0018] Further, the single-crystal positive electrode material has a median particle size D502 of 1~3 μm.
[0019] Further, D502=D501×0.414.
[0020] Further, the positive electrode material substrate includes at least one of a nickel-cobalt-manganese lithium cathode material, a nickel-cobalt-aluminum lithium cathode material and a lithium-rich manganese-based cathode material.
[0021] Further, the positive electrode material substrate contains a doping element A, wherein A includes at least one of Nb, Mo, Ti, Y and Zr elements.
[0022] Further, the doping amount of the doping element A is 500~2000 ppm.
[0023] The application further provides a preparation method of the halide-sulfide double-layer coated positive electrode material, comprising the following steps: mixing raw materials for preparing a halide electrolyte coating layer after first crushing with a positive electrode material substrate, and / or spraying raw materials for preparing a halide electrolyte coating layer to the surface of the positive electrode material substrate after mixing the raw materials with a first solvent; then performing first heat treatment to obtain a halide coated positive electrode material. Mixing raw materials for preparing a sulfide electrolyte coating layer after second crushing with the halide coated positive electrode material, and / or spraying raw materials for preparing a sulfide electrolyte coating layer to the surface of the halide coated positive electrode material after mixing the raw materials with a second solvent; then performing second heat treatment to obtain the halide-sulfide double-layer coated positive electrode material.
[0024] Further, the first crushing is to a particle size range of 20-50 nm.
[0025] Further, the first solvent comprises at least one of water, ethanol, acetonitrile and tetrahydrofuran.
[0026] Further, the first heat treatment is at a temperature of 120-250℃, and the holding time of the first heat treatment is 4-12 h.
[0027] Further, the second crushing is to a particle size range of 20-50 nm.
[0028] Further, the second solvent comprises at least one of water, ethanol, acetonitrile and tetrahydrofuran.
[0029] Further, the second heat treatment is at a temperature of 400-500℃, and the holding time of the second heat treatment is 4-12 h.
[0030] Further, the preparation method of the positive electrode material substrate comprises: sintering mixed materials at 700-900℃ for 8-20 h; wherein the mixed materials comprise a precursor and a lithium source, or the mixed materials comprise a precursor, a lithium source and a dopant; the dopant contains at least one of Nb, Mo, Ti, Y and Zr elements.
[0031] The application further provides a full solid-state battery comprising the halide-sulfide double-layer coated positive electrode material.
[0032] The application further provides an electric device comprising the full solid-state battery.
[0033] Compared with the prior art, the application has the following beneficial effects:
[0034] (1) The halide sulfide double-layer coated positive electrode material proposed in the application has the interface stability with the solid-state electrolyte and good chemical stability. The inner layer halide electrolyte has high oxidation potential resistance and no side reaction problem when contacting the positive electrode, and can maintain stable interface contact; the outer layer sulfide electrolyte coated on the halide electrolyte overcomes the problems of poor air stability and high density of the halide electrolyte. In addition, the appropriate halide electrolyte coating amount can inhibit the side reaction of the sulfide and the positive electrode material, and avoid the performance deterioration problem caused by the halide environment side reaction and high density; the appropriate amount of sulfide electrolyte coating is conducive to reducing the side reaction of the halide electrolyte, and constructing a better ion transport path in the electrode, while avoiding the problem of large electronic transport impedance caused by excessive coating amount.
[0035] (2) The halide sulfide double-layer coated positive electrode material of the application has important significance for improving the energy density, rate performance and cycle life of the all-solid-state battery. DETAILED DESCRIPTION
[0036] The technical solutions of the application will be described clearly and completely in combination with specific embodiments, but those skilled in the art will understand that the following described embodiments are part of the embodiments of the application, not all the embodiments, and are only used to illustrate the application, and should not be regarded as limiting the scope of the application. Based on the embodiments in the application, all other embodiments obtained by those skilled in the art without creative labor are within the scope of protection of the application. If the specific conditions are not specified in the embodiments, the conventional conditions or the conditions recommended by the manufacturer are used. If the reagents or instruments used are not specified by the manufacturer, they are all conventional products that can be purchased on the market.
[0037] If not specifically stated, in the application, "first aspect", "second aspect", "third aspect", "fourth aspect" and the like are only used for description purposes, and cannot be understood as indicating or implying relative importance or quantity, nor can it be understood as implicitly indicating the importance or quantity of the indicated technical features. Moreover, "first", "second", "third", "fourth" and the like only serve the purpose of non-exhaustive enumeration and description, and should be understood as not constituting a closed limitation on the quantity.
[0038] If not specifically stated, the "includes" and "contains" mentioned in the application mean open-ended, and can also be closed. For example, the "includes" and "contains" can mean that other components not listed can also be included or contained, or only the listed components can be included or contained.
[0039] If not specifically stated, in the application, "one or more" or "at least one" means any one, any two or any two or more of the listed items. Among them, "several" means any two or more.
[0040] In a first aspect, to solve the problems of high density and poor air stability of halide electrolyte and poor oxidation stability of sulfide electrolyte, the application provides a halide-sulfide double-layer coated positive electrode material, which comprises a positive electrode material substrate and a halide electrolyte coating layer and a sulfide electrolyte coating layer successively coated on the positive electrode material substrate. That is, the halide electrolyte coating layer coats the positive electrode material substrate as an intermediate layer. The sulfide electrolyte coating layer coats the halide electrolyte coating layer as an outer layer.
[0041] It can be understood that the halide electrolyte coating layer is mainly composed of halide electrolyte. The sulfide electrolyte coating layer is mainly composed of sulfide electrolyte.
[0042] The halide-sulfide double-layer coated positive electrode material provided by the application has the interface stability with solid-state electrolyte and good chemical stability. Specifically, the halide electrolyte in the inner layer has high oxidation potential resistance and no side reaction problem when contacting the positive electrode, and can maintain stable interface contact; the sulfide electrolyte in the outer layer coats the halide electrolyte, overcoming the problems of poor air stability and high density of halide electrolyte.
[0043] The halide-sulfide double-layer coated positive electrode material of the application is of great significance to improve the energy density, rate performance and cycle life of the full solid-state battery.
[0044] The mass of the halide electrolyte coating layer is 0.5% to 1% of the mass of the positive electrode material substrate, including but not limited to any one of 0.5%, 0.6%, 0.7%, 0.8%, 0.9% and 1% or a range value between any two of them. The appropriate halide electrolyte coating amount can inhibit the side reaction of sulfide and positive electrode material, and avoid the performance deterioration problem caused by halide environmental side reaction and high density.
[0045] The mass of the sulfide electrolyte coating layer is 2% to 5% of the mass of the positive electrode material substrate, including but not limited to any one of 2%, 2.5%, 3%, 3.5%, 4%, 4.5% and 5% or a range value between any two of them. The appropriate amount of sulfide electrolyte coating is conducive to reducing the side reaction of halide electrolyte, constructing better ion transport path in the electrode, and avoiding the problem of large electronic transport impedance caused by excessive coating amount.
[0046] In some specific embodiments, the halide electrolyte coating layer comprises a chemical formula of Li z MX 6-v G vMxGzSv, wherein M comprises at least one of Y, Yb, Zr, In, Sc, Ta and La elements, X comprises at least one of Cl, Br and I elements, G comprises at least one of O, N and F elements, 2≤z≤4, 0.1≤v≤0.5. The halide electrolyte has a higher oxidation potential (greater than 4.2V), thereby being stable at the interface with the ternary positive electrode material, avoiding the problem of increased interface impedance caused by the sulfide electrolyte oxidizing and decomposing on the surface of the positive electrode material.
[0047] wherein z comprises but is not limited to a point value of any one of 2, 3, 4 or a range value between any two of them; v comprises but is not limited to a point value of any one of 0.1, 0.2, 0.3, 0.4, 0.5 or a range value between any two of them.
[0048] In some specific embodiments, the material of the sulfide electrolyte coating layer comprises at least one of a first sulfide electrolyte, an oxygen-doped modified material of the first sulfide electrolyte, a second sulfide electrolyte, an oxygen-doped modified material of the second sulfide electrolyte.
[0049] wherein the oxygen-doped modified material of the first sulfide electrolyte refers to the first sulfide electrolyte doped with O element; the oxygen-doped modified material of the second sulfide electrolyte refers to the second sulfide electrolyte doped with O element. Preferably, the doping molar amount of the doping element O in the oxygen-doped modified material of the first sulfide electrolyte and / or the oxygen-doped modified material of the second sulfide electrolyte is 0.1-0.5.
[0050] wherein the chemical formula of the first sulfide electrolyte is Li (6-x) PS (5-x) Q (1+x) Q comprises at least one of Cl, Br and I elements, 0≤x≤0.6, x comprises but is not limited to a point value of any one of 0, 0.1, 0.2, 0.3, 0.4, 0.5, 0.6 or a range value between any two of them.
[0051] The chemical formula of the second sulfide electrolyte is yLi2S·(1-y)P2S5, 0.2≤y≤0.8, y comprises but is not limited to a point value of any one of 0.2, 0.3, 0.4, 0.5, 0.6, 0.7, 0.8 or a range value between any two of them.
[0052] The first sulfide electrolyte and the second sulfide electrolyte have the advantages of high ionic conductivity, low density and good environmental stability, and the full solid-state battery using the sulfide electrolyte has higher energy density, rate performance and cycle life.
[0053] In some specific embodiments, the positive electrode material matrix comprises both polycrystalline positive electrode material and single-crystal positive electrode material, i.e. contains both polycrystalline positive electrode material and single-crystal positive electrode material, which is conducive to improving the dense packing of the positive electrode material, thereby reducing the use of solid-state electrolyte material inside the electrode and improving the energy density of the battery cell.
[0054] In some specific embodiments, the mass ratio of the polycrystalline positive electrode material to the single-crystal positive electrode material is 6-8:2-4, for example 6:4, 7:3 or 8:2.
[0055] In some specific embodiments, the polycrystalline positive electrode material comprises secondary particles formed by aggregation of primary particles. The secondary particles have a median particle size D501 of 3-7 μm, including but not limited to any one of 3 μm, 4 μm, 5 μm, 6 μm, 7 μm or a range value between any two of them; and the primary particles have a median particle size of 300-500 nm, including but not limited to any one of 300 nm, 350 nm, 400 nm, 450 nm, 500 nm or a range value between any two of them. The use of polycrystalline positive electrode material with a specific particle size is conducive to the interface contact between the positive electrode material and the sulfide electrolyte, forming a more continuous ion transmission path and improving the rate performance of the battery cell.
[0056] In some specific embodiments, the single-crystal positive electrode material has a median particle size D502 of 1-3 μm, including but not limited to any one of 1 μm, 1.5 μm, 2 μm, 2.5 μm, 3 μm or a range value between any two of them. The use of single-crystal positive electrode material with a specific particle size is conducive to forming a densest packing structure with the polycrystalline positive electrode material, thereby improving the electrode packing, reducing the amount of solid-state electrolyte material and improving the energy density.
[0057] In some specific embodiments, the median particle size D502 of the single-crystal positive electrode material and the median particle size D501 of the secondary particles of the polycrystalline positive electrode material satisfy the following relationship: D502 = D501 × 0.414. This is conducive to particle dense packing matching, thereby improving the energy density.
[0058] In some specific embodiments, the positive electrode material matrix comprises at least one of lithium nickel cobalt manganese oxide positive electrode material (NCM), lithium nickel cobalt aluminum oxide positive electrode material (NCA) and lithium-rich manganese-based positive electrode material.
[0059] In some specific embodiments, the positive electrode material matrix contains a doping element A, wherein A comprises at least one of Nb, Mo, Ti, Y and Zr elements. Doping A can improve the ion transport capacity and structural stability.
[0060] In some specific embodiments, the doping amount of the doping element A is 500-2000 ppm, including but not limited to any one of 500 ppm, 1000 ppm, 1500 ppm, 2000 ppm or a range value between any two of them. Wherein, 10000 ppm = 1 wt.%.
[0061] In a second aspect, the present application provides a preparation method of a halide-sulfide double-layer coated positive electrode material, comprising the following steps:
[0062] The raw material for preparing the halide electrolyte coating layer is mixed with the positive electrode material substrate after first crushing, and / or the raw material for preparing the halide electrolyte coating layer is mixed with the first solvent and then sprayed onto the surface of the positive electrode material substrate; then first heat treatment is carried out to obtain the halide coated positive electrode material.
[0063] Specifically, the raw material for preparing the halide electrolyte coating layer is first crushed (pulverized) and uniformly mixed, and then the mixed raw material for preparing the halide electrolyte coating layer is mixed with the positive electrode material substrate by a mechanical fusion machine to coat the raw material for preparing the halide electrolyte coating layer onto the surface of the positive electrode material substrate, and then first heat treatment is carried out to obtain the halide coated positive electrode material. And / or, the raw material for preparing the halide electrolyte coating layer is dissolved or dispersed in the first solvent, and then the solution or dispersion is sprayed onto the surface of the positive electrode material substrate by a fluidized bed, and then first heat treatment is carried out to obtain the halide coated positive electrode material. Wherein, the halide coated positive electrode material refers to a composite material in which the halide electrolyte coating layer is coated on the outer surface of the positive electrode material substrate.
[0064] The raw material for preparing the sulfide electrolyte coating layer is mixed with the halide coated positive electrode material after second crushing, and / or the raw material for preparing the sulfide electrolyte coating layer is mixed with the second solvent and then sprayed onto the surface of the halide coated positive electrode material; then second heat treatment is carried out to obtain the halide-sulfide double-layer coated positive electrode material.
[0065] Specifically, the raw material for preparing the sulfide electrolyte coating layer is second crushed (pulverized) and uniformly mixed, and then the mixed raw material for preparing the sulfide electrolyte coating layer is mixed with the halide coated positive electrode material by a mechanical fusion machine to coat the raw material for preparing the sulfide electrolyte coating layer onto the surface of the halide coated positive electrode material, and then second heat treatment is carried out to obtain the halide-sulfide double-layer coated positive electrode material. And / or, the raw material for preparing the sulfide electrolyte coating layer is dissolved or dispersed in the second solvent, and then the solution or dispersion is sprayed onto the surface of the halide coated positive electrode material by a fluidized bed, and then second heat treatment is carried out to obtain the halide-sulfide double-layer coated positive electrode material.
[0066] The method can obtain a positive electrode material with a double-layer coating, wherein the halide electrolyte coating layer is an inner layer coated on the outer surface of the positive electrode material substrate, and the sulfide electrolyte coating layer is an outer layer coated on the halide electrolyte coating layer. The halide-sulfide double-layer coated positive electrode material has high interface stability and good chemical stability.
[0067] In addition, the preparation method has the advantages of simple operation, short process, low cost, and suitability for batch production.
[0068] In some specific embodiments, the method of the first crushing and / or the second crushing includes, but is not limited to, pulverization.
[0069] In some specific embodiments, the first crushing is to a particle size range of 20-50 nm of the material, including but not limited to any one of 20 nm, 25 nm, 30 nm, 35 nm, 40 nm, 45 nm, 50 nm, or a range value between any two of them. This is conducive to the formation of a uniform coating layer on the surface of the positive electrode by a small amount of halide electrolyte raw materials.
[0070] In some specific embodiments, the first solvent includes at least one of water, ethanol, acetonitrile, and tetrahydrofuran.
[0071] In some specific embodiments, the temperature of the first heat treatment is 120-250°C, including but not limited to any one of 120°C, 130°C, 150°C, 160°C, 180°C, 200°C, 230°C, 250°C, or a range value between any two of them; and the holding time of the first heat treatment is 4-12 h, including but not limited to any one of 4 h, 5 h, 6 h, 8 h, 10 h, 12 h, or a range value between any two of them.
[0072] In some specific embodiments, the first heat treatment is performed under vacuum conditions.
[0073] In some specific embodiments, the second crushing is to a particle size range of 20-50 nm of the material, including but not limited to any one of 20 nm, 25 nm, 30 nm, 35 nm, 40 nm, 45 nm, 50 nm, or a range value between any two of them.
[0074] The particle size range of 20-50 nm means that the particle size of the material is in the range of 20-50 nm.
[0075] In some specific embodiments, the second solvent includes at least one of water, ethanol, acetonitrile, and tetrahydrofuran.
[0076] In some specific embodiments, the temperature of the second heat treatment is 400-500℃, including but not limited to any one of 400℃, 430℃, 450℃, 480℃, 500℃, or a range value between any two of them; the holding time of the second heat treatment is 4-12h, including but not limited to any one of 4h, 5h, 6h, 8h, 10h, 12h, or a range value between any two of them.
[0077] In some specific embodiments, the preparation method of the positive electrode material substrate comprises: sintering the mixed material at 700-900℃ for 8-20h, and obtaining the positive electrode material substrate after cooling. The sintering temperature includes but is not limited to any one of 700℃, 750℃, 800℃, 850℃, 900℃, or a range value between any two of them; the holding time of sintering includes but is not limited to any one of 8h, 10h, 12h, 15h, 18h, 20h, or a range value between any two of them.
[0078] The mixed material comprises a precursor and a lithium source, or the mixed material comprises a precursor, a lithium source and a dopant; the dopant contains at least one of Nb, Mo, Ti, Y and Zr elements.
[0079] In some specific embodiments, the lithium source comprises a lithium-containing compound commonly used in the art, such as lithium carbonate, but is not limited thereto.
[0080] In a third aspect, the present application provides a full solid-state battery comprising a halide sulfide double-coated positive electrode material.
[0081] The full solid-state battery has high energy density, good rate performance and long cycle life.
[0082] In some specific embodiments, the negative electrode material of the full solid-state battery is selected from one of graphite, nano, silicon-carbon and no negative electrode.
[0083] In a fourth aspect, the present application provides a power-using device comprising a full solid-state battery.
[0084] The power-using device refers to a device or equipment containing the full solid-state battery described above.
[0085] The power consuming device of the present application is not particularly limited, and can include, but is not limited to, the following kinds: notebook computers, pen-input computers, mobile computers, electronic book players, portable telephones, portable facsimile machines, portable copiers, portable printers, head-mounted stereo headphones, video recorders, liquid crystal televisions, portable cleaners, portable CD players, mini-disc players, transceivers, electronic organizers, calculators, memory cards, portable audio players, radios, backup power supplies, motors, automobiles, motorcycles, power-assisted bicycles, bicycles, lighting appliances, toys, game machines, timepieces, power tools, flashlights, cameras, household large-size storage batteries, and the like.
[0086] Embodiments of the present application will be described in detail below with reference to Examples, but those skilled in the art will appreciate that the following Examples are illustrative only and should not be viewed as limiting the scope of the present application. Where specific conditions are not mentioned in the Examples, they are carried out under conventional conditions or conditions recommended by the manufacturer. Where the manufacturer of a reagent or instrument is not mentioned, it is a conventional product that can be obtained commercially.
[0087] Example 1
[0088] The preparation method of the halide-sulfide double-coated positive electrode material provided in this Example includes the following steps:
[0089] (1) Synthesis of positive electrode material base: Ni 0.8 Co 0.1 Mn 0.1 (OH)2precursor, lithium carbonate, and niobium oxide are mixed uniformly and then sintered at 800°C for 12 h to obtain a positive electrode material base having the chemical formula LiNi 0.8 Co 0.1 Mn 0.1 O2, wherein the Nb element doping amount is 1500 ppm. The positive electrode material base includes a mixture of polycrystalline positive electrode material and single-crystal positive electrode material, wherein the mass ratio of the polycrystalline positive electrode material to the single-crystal positive electrode material is 7:3; the polycrystalline positive electrode material includes secondary particles formed by aggregation of primary particles, wherein the secondary particles have a median particle size D501= 5 μm and the primary particles have a median particle size of 400 nm; and the single-crystal positive electrode material has a median particle size D502= 2 μm, satisfying D502= D501x 0.414.
[0090] (2) Coating of halide electrolyte Li 2.2 Zr 0.8 In 0.2 Cl 5.8 F 0.2 F: Li 2.2 Zr 0.8 In 0.2 Cl 5.8 F 0.2The mixed material is obtained by mixing and crushing (i.e., first crushing) the raw materials in a stoichiometric ratio to a particle size range of 20-50 nm. Then, the mixed material is mixed with the positive electrode material matrix by using a mechanical fusion machine to make the mixed material coat the surface of the positive electrode material matrix, wherein the mass of the mixed material is 0.8% of the mass of the positive electrode material matrix. The mixed coated material is then vacuum heat treated at 150°C for 6h (i.e., first heat treatment) to obtain the halide coated positive electrode material.
[0091] (3) Coating of the sulfide electrolyte Li6PS5Cl: Lithium sulfide, diphosphorus pentasulfide and lithium chloride are mixed in a Li6PS5Cl ratio and crushed (i.e., second crushing) to a particle size range of 20-50 nm to obtain a mixture. Then, the mixture is mixed with the halide coated positive electrode material by using a mechanical fusion machine to make the mixture coat the surface of the halide coated positive electrode material, wherein the mass of the mixture is 2% of the mass of the positive electrode material matrix. Subsequently, the mixture is calcined at 420°C for 10h (i.e., second heat treatment) to obtain the halide-sulfide double-layer coated positive electrode material.
[0092] The halide-sulfide double-layer coated positive electrode material comprises a positive electrode material matrix and a halide electrolyte coating layer and a sulfide electrolyte coating layer which coat the positive electrode material matrix in sequence. That is, the halide-sulfide double-layer coated positive electrode material has a double-layer coating layer, wherein the halide electrolyte coating layer coats the positive electrode material matrix, and the sulfide electrolyte coating layer coats the halide electrolyte coating layer.
[0093] Example 2
[0094] The preparation method of the halide-sulfide double-layer coated positive electrode material provided in this example is basically the same as that in Example 1, except that in step (2), the chemical formula of the halide electrolyte is replaced by Li 2.2 Zr 0.8 In 0.2 Cl 5.8 O 0.1 , and the raw materials and their proportions are adaptively adjusted.
[0095] Example 3
[0096] The preparation method of the halide-sulfide double-layer coated positive electrode material provided in this example is basically the same as that in Example 1, except that in step (2), the chemical formula of the halide electrolyte is replaced by Li 2.2 Zr 0.8 In 0.2 Cl 5.8 F 0.1 O 0.05 , and the raw materials and their proportions are adaptively adjusted.
[0097] Example 4
[0098] The preparation method of the halide sulfide double-layer coated positive electrode material provided in this embodiment is basically the same as that in Embodiment 1, except that in step (2), the mass of the mixed material is 0.5% of the mass of the positive electrode material matrix.
[0099] Embodiment 5
[0100] The preparation method of the halide sulfide double-layer coated positive electrode material provided in this embodiment is basically the same as that in Embodiment 1, except that in step (2), the mass of the mixed material is 1% of the mass of the positive electrode material matrix.
[0101] Embodiment 6
[0102] The preparation method of the halide sulfide double-layer coated positive electrode material provided in this embodiment is basically the same as that in Embodiment 1, except that in step (3), the chemical formula of the sulfide electrolyte is replaced by Li6PS 4.9 ClO 0.1 , and the raw materials and their proportions are adjusted adaptively.
[0103] Embodiment 7
[0104] The preparation method of the halide sulfide double-layer coated positive electrode material provided in this embodiment is basically the same as that in Embodiment 1, except that in step (3), the chemical formula of the sulfide electrolyte is replaced by Li 5.5 PS 4.4 Cl 1.5 O 0.1 , and the raw materials and their proportions are adjusted adaptively.
[0105] Embodiment 8
[0106] The preparation method of the halide sulfide double-layer coated positive electrode material provided in this embodiment is basically the same as that in Embodiment 1, except that in step (3), the mass of the mixture is 3.5% of the mass of the positive electrode material matrix.
[0107] Embodiment 9
[0108] The preparation method of the halide sulfide double-layer coated positive electrode material provided in this embodiment is basically the same as that in Embodiment 1, except that in step (3), the mass of the mixture is 5% of the mass of the positive electrode material matrix.
[0109] Embodiment 10
[0110] The preparation method of the halide sulfide double-layer coated positive electrode material provided in this embodiment is basically the same as that in Embodiment 1, except that in step (1), the positive electrode material matrix is a pure polycrystalline positive electrode material.
[0111] Embodiment 11
[0112] The preparation method of the halide-sulfide double-layer coated positive electrode material provided by the embodiment comprises the following steps:
[0113] (1) The same as step (1) of Example 1.
[0114] (2) Coating of halide electrolyte Li 2.2 Zr 0.8 In 0.2 Cl 5.8 F 0.2 : Lithium chloride, zirconium chloride, indium chloride and lithium fluoride are mixed in a stoichiometric ratio and dissolved in deionized water (i.e. the first solvent), and then the solution is sprayed onto the surface of the positive electrode material substrate through a fluidized bed, the sum of the masses of lithium chloride, zirconium chloride, indium chloride and lithium fluoride in the solution being 0.8% of the mass of the positive electrode material substrate, and then vacuum heat treatment at 250°C for 4h (i.e. the first heat treatment) is performed, to obtain a halide-coated positive electrode material. 2.2 Zr 0.8 In 0.2 Cl 5.8 F 0.2 : Lithium chloride, zirconium chloride, indium chloride and lithium fluoride are mixed in a stoichiometric ratio and dissolved in deionized water (i.e. the first solvent), and then the solution is sprayed onto the surface of the positive electrode material substrate through a fluidized bed, the sum of the masses of lithium chloride, zirconium chloride, indium chloride and lithium fluoride in the solution being 0.8% of the mass of the positive electrode material substrate, and then vacuum heat treatment at 250°C for 4h (i.e. the first heat treatment) is performed, to obtain a halide-coated positive electrode material.
[0115] (3) Coating of sulfide electrolyte Li6PS5Cl: Lithium sulfide, phosphorus pentasulfide and lithium chloride are mixed in a Li6PS5Cl ratio and dissolved in deionized water (i.e. the second solvent), and then the solution is sprayed onto the surface of the halide-coated positive electrode material through a fluidized bed, the sum of the masses of lithium sulfide, phosphorus pentasulfide and lithium chloride in the solution being 2% of the mass of the positive electrode material substrate, and then calcination at 500°C for 6h (i.e. the second heat treatment) is performed, to obtain a halide-sulfide double-layer coated positive electrode material.
[0116] Comparative Example 1
[0117] The positive electrode material provided by the present comparative example is the positive electrode material substrate prepared in step (1) of Example 1, i.e. the positive electrode material has no coating layer on the surface.
[0118] Comparative Example 2
[0119] The positive electrode material provided by the present comparative example is the halide-coated positive electrode material prepared in step (2) of Example 1. That is, the structure of the positive electrode material of the present comparative example is that a halide electrolyte coating layer is coated on the outer surface of the positive electrode material substrate, and there is no sulfide electrolyte coating layer.
[0120] Comparative Example 3
[0121] The preparation method of the positive electrode material provided by the present comparative example is basically the same as that of Example 1, except that step (2) is not performed, and instead the mixture of lithium sulfide, phosphorus pentasulfide and lithium chloride is directly mixed with the positive electrode material matrix to coat the mixture onto the surface of the positive electrode material matrix. That is, the structure of the positive electrode material prepared in the present comparative example is that the sulfide electrolyte layer is coated on the outer surface of the positive electrode material matrix, and there is no halide electrolyte coating layer.
[0122] Comparative Example 4
[0123] The preparation method of the positive electrode material provided by the present comparative example includes the following steps:
[0124] (1) The same as step (1) of Example 1.
[0125] (2) Coating of the sulfide electrolyte Li6PS5Cl: Lithium sulfide, phosphorus pentasulfide and lithium chloride are mixed in the ratio of Li6PS5Cl, and are pulverized to a particle size range of 20-50 nm to obtain a mixture. Then, a mechanical fusion machine is used to mix the mixture with the positive electrode material matrix to coat the mixture onto the surface of the positive electrode material matrix, wherein the mass of the mixture is 2% of the mass of the positive electrode material matrix, and then calcination is performed at 420°C for 10h to obtain a sulfide-coated positive electrode material.
[0126] (3) Coating of the halide electrolyte Li 2.2 Zr 0.8 In 0.2 Cl 5.8 F 0.2 : Lithium chloride, zirconium chloride, indium chloride and lithium fluoride are mixed in the stoichiometric ratio of Li 2.2 Zr 0.8 In 0.2 Cl 5.8 F 0.2 , and are pulverized to a particle size range of 20-50 nm to obtain a mixed material. Then, a mechanical fusion machine is used to mix the mixed material with the sulfide-coated positive electrode material to coat the mixed material onto the surface of the sulfide-coated positive electrode material, wherein the mass of the mixed material is 0.8% of the mass of the positive electrode material matrix, and then the mixed coated material is vacuum heat treated at 150°C for 6h to obtain a positive electrode material.
[0127] The positive electrode material prepared in the present comparative example includes a positive electrode material matrix, and a sulfide electrolyte coating layer and a halide electrolyte coating layer which are sequentially coated on the positive electrode material matrix. That is, the halide-sulfide double-coated positive electrode material has a double-coating layer, wherein the sulfide electrolyte coating layer coats the positive electrode material matrix, and the halide electrolyte coating layer coats the sulfide electrolyte coating layer.
[0128] Experimental Example
[0129] The halide sulfide double-layer coated positive electrode material prepared by each embodiment and the positive electrode material of each comparative example were respectively made into a grinding tool battery according to the following method: Li6PS5Cl with a median particle size of 3 μm was placed in a grinding tool battery to make a 1 mm electrolyte original piece under a pressure of 30 MPa; the halide sulfide double-layer coated positive electrode material was mixed with Li6PS5Cl with a median particle size of 1 μm at a mass ratio of 9:1 and placed on one side of the electrolyte original piece, and then a lithium-indium alloy piece was attached on the other side. The operating environment was a dew point of -50°C.
[0130] The grinding tool batteries were respectively subjected to electrochemical tests: (1) specific capacity and initial efficiency test: charging and discharging at a rate of 0.1C, the 0.1C discharge specific capacity was the material specific capacity, and the initial discharge capacity divided by the initial charge capacity was the initial efficiency (the first coulombic efficiency); (2) rate retention rate: charging at 0.1C and discharging at 0.1C and 1C, and the 1C discharge capacity divided by the 0.1C discharge capacity was the rate retention rate; (3) cycle life: charging at 1C and discharging at 1C until the cycle number at which the capacity decayed to 80%. The test results are shown in Table 1.
[0131] Table 1 Electrochemical test results of the grinding tool batteries
[0132]
[0133] As can be seen from Table 1, the grinding tool batteries assembled by using the halide sulfide double-layer coated positive electrode material prepared by each embodiment have high specific capacity, high initial efficiency, high rate retention rate, and longer cycle life.
[0134] Comparative Example 1 has no coating layer, which leads to a significant decrease in the specific capacity, initial efficiency and rate retention rate of the assembled grinding tool battery, and a significant shortening of the cycle life.
[0135] Comparative Example 2 has no sulfide electrolyte coating layer, which leads to serious side reactions of the halide electrolyte in a dry environment and deterioration of the electrochemical performance.
[0136] Comparative Example 3 has no halide electrolyte coating layer, which leads to a large side reaction between the sulfide electrolyte and the positive electrode material, an increase in impedance, and deterioration of the electrochemical performance.
[0137] Comparative Example 4 has a sulfide electrolyte coating layer in the inner layer and a halide electrolyte coating layer in the outer layer, which leads to the problems of side reactions between the sulfide and the positive electrode and chemical reactions of the halide in a dry environment, and a sharp deterioration of the performance.
[0138] In summary, the halide sulfide double-layer coated positive electrode material has the interface stability with the solid-state electrolyte and good chemical stability. The inner layer halide electrolyte has high oxidation potential resistance, no side reaction problem with the positive electrode, and can maintain stable interface contact. The outer layer sulfide electrolyte coated halide electrolyte overcomes the problems of poor air stability and high density of the halide electrolyte.
[0139] Therefore, the halide sulfide double-layer coated positive electrode material has important significance for improving the energy density, rate performance and cycle life of the all-solid-state battery.
[0140] Although the present application has been illustrated and described with reference to specific embodiments, it is realized that the above examples are merely illustrative of the technical solutions of the present application, and are not limiting thereof; it should be understood by those skilled in the art that the technical solutions recorded in the above embodiments can be modified, or some or all of the technical features can be replaced equivalently, without departing from the spirit and scope of the present application; and these modifications or replacements do not make the essence of the corresponding technical solutions deviate from the scope of the technical solutions of the embodiments of the present application; therefore, this means that all these replacements and modifications within the scope of the present application are included in the appended claims.
Claims
1. A halide-sulfide double-coated positive electrode material, characterized by, The positive electrode material substrate comprises a halide electrolyte coating layer and a sulfide electrolyte coating layer successively coated on the positive electrode material substrate; The mass of the halide electrolyte coating layer is 0.5%-1% of the mass of the positive electrode material substrate; The mass of the sulfide electrolyte coating layer is 2%-5% of the mass of the positive electrode material substrate; The positive electrode material substrate comprises polycrystalline positive electrode material and single-crystal positive electrode material; The polycrystalline positive electrode material comprises secondary particles formed by aggregation of primary particles, wherein the secondary particles have a median particle size D501 of 3-7 μm, and the primary particles have a median particle size of 300-500 nm; The single-crystal positive electrode material has a median particle size D502 of 1-3 μm; D502=D501×0.414; The positive electrode material substrate contains a doping element A, wherein A comprises at least one of Nb, Mo, Ti, Y and Zr elements, and the doping amount of the doping element A is 500-2000 ppm.
2. The halide-sulfide double-coated cathode material of claim 1, wherein, The halide electrolyte coating layer includes a material of a chemical formula of Li z MX 6-v G v wherein M includes at least one of Y, Yb, Zr, In, Sc, Ta, and La elements, X includes at least one of Cl, Br, and I elements, G includes at least one of O, N, and F elements, 2≤z≤4, and 0.1≤v≤0.
5.
3. The halide-sulfide double-coated cathode material of claim 1, wherein, The material of the sulfide electrolyte coating layer comprises at least one of a first sulfide electrolyte or an oxygen-doped modified material thereof, a second sulfide electrolyte or an oxygen-doped modified material thereof; wherein the chemical formula of the first sulfide electrolyte is Li (6-x) PS (5-x) Q (1+x) Q comprises at least one of Cl, Br and I elements, and 0≤x≤0.6; the chemical formula of the second sulfide electrolyte is yLi2S·(1-y)P2S5, and 0.2≤y≤0.
8.
4. The halide-sulfide double-layer coated cathode material according to any one of claims 1 to 3, characterized in that, At least one of the following conditions is met: (1) The mass ratio of the polycrystalline positive electrode material to the single-crystal positive electrode material is 6-8:2-4; (2) The positive electrode material substrate comprises at least one of lithium nickel cobalt manganese oxide, lithium nickel cobalt aluminum oxide and lithium-rich manganese-based positive electrode material.
5. The method of producing a halide-sulfide double-coated positive electrode material according to any one of claims 1 to 4, characterized by, The method comprises the following steps: The raw material for preparing the halide electrolyte coating layer is mixed with the positive electrode material substrate after first crushing, and / or the raw material for preparing the halide electrolyte coating layer is mixed with a first solvent and then sprayed onto the surface of the positive electrode material substrate; then first heat treatment is performed to obtain the halide-coated positive electrode material; The raw material for preparing the sulfide electrolyte coating layer is mixed with the halide-coated positive electrode material after second crushing, and / or the raw material for preparing the sulfide electrolyte coating layer is mixed with a second solvent and then sprayed onto the surface of the halide-coated positive electrode material; then second heat treatment is performed to obtain the halide-sulfide double-layer-coated positive electrode material.
6. The method for preparing the halide-sulfide bilayer coated cathode material according to claim 5, characterized in that, At least one of the following conditions is met: (1) The particle size range of the material after the first crushing is 20-50 nm; (2) The first solvent comprises at least one of water, ethanol, acetonitrile and tetrahydrofuran; (3) The temperature of the first heat treatment is 120-250 ℃, and the holding time of the first heat treatment is 4-12 h.
7. The method for preparing the halide-sulfide bilayer coated cathode material according to claim 5, characterized in that, At least one of the following conditions is met: (1) The particle size range of the material after the second crushing is 20-50 nm; (2) The second solvent comprises at least one of water, ethanol, acetonitrile and tetrahydrofuran; (3) The temperature of the second heat treatment is 400-500 ℃, and the holding time of the second heat treatment is 4-12 h.
8. The method for preparing the halide-sulfide bilayer coated cathode material according to claim 5, characterized in that, The preparation method of the positive electrode material substrate comprises sintering mixed materials at 700-900 ℃ for 8-20 h; wherein the mixed materials comprise a precursor and a lithium source, or the mixed materials comprise a precursor, a lithium source and a dopant; the dopant contains at least one of Nb, Mo, Ti, Y and Zr elements.
9. An all-solid battery, characterized by, The halide-sulfide double-layer-coated positive electrode material according to any one of claims 1-4.
10. An electric device, characterized by The all-solid-state battery according to claim 9.
Citation Information
Patent Citations
Method for coating high-voltage positive electrode material with double-layer solid electrolyte
CN118117073A
Process for production of sulfide solid electrolyte material, and process for production of lithium solid-state battery
CN102959646A
Preparation method of long-life solid-state battery high-nickel composite positive electrode
CN115084450A
Positive electrode material and preparation method thereof, battery and electric device
CN119447231A